The role of chemical synthesis in developing RiPP antibiotics. (26th February 2021) - Rowe, Sam M.; Spring, David R.
Abstract : This tutorial review discusses the potential of ribosomally synthesised and post-translationally modified peptides (RiPPs) as antimicrobials and looks at the chemical synthesis of three classes of RiPP: lasso peptides, cyclotides, and lanthipeptides. Abstract : The growing antimicrobial resistance crisis necessitates the discovery and development of novel classes of antibiotics if a 'postantibiotic era' is to be avoided. Ribosomally synthesised and post-translationally modified peptides, or RiPPs, are becoming increasingly recognised as a potential source of antimicrobial drugs. This is due to a combination of their potent antimicrobial activity and their high stability relative to unmodified linear peptides. However, as peptide drugs, their clinical development is often perturbed by issues such as low solubility and poor bioavailability. Chemical synthesis has the potential to overcome some of these challenges. Furthermore, the structural complexity of RiPPs makes them interesting synthetic targets in their own right, with the total synthesis of some structural classes having only been recently realised. This review focusses on the use of RiPPs as antimicrobial agents and will highlight various strategies that have been employed to chemically synthesise three major classes of RiPPs: lasso peptides, cyclotides, and lanthipeptides.